2011
DOI: 10.1074/jbc.m110.186031
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Self-assembly of the Cellulosome Enzyme Complex

Abstract: Most bacteria use free enzymes to degrade plant cell walls in nature. However, some bacteria have adopted a different strategy wherein enzymes can either be free or tethered on a protein scaffold forming a complex called a cellulosome. The study of the structure and mechanism of these large macromolecular complexes is an active and ongoing research topic, with the goal of finding ways to improve biomass conversion using cellulosomes. Several mechanisms involved in cellulosome formation remain unknown, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 73 publications
(51 reference statements)
0
42
0
Order By: Relevance
“…These data suggested that preferential binding of cellulosomal enzymes to the cohesin modules did not result from slight differences in the binding affinity between the cohesin and dockerin modules, but rather, resulted from differences in the length of the intercohesin linker: a shorter intercohesin linker promoted preferential binding. Furthermore, computational simulations of the C. thermocellum cellulosome assembled with three cellulosomal enzymes (Cbh9A, Cel5B, and Cel48S) suggested that large multimodular enzymes (Cbh9A) may bind more frequently to CipA than smaller, single-modular enzymes (Cel5B or Cel48S) (37). Because CipA contains intercohesin linkers of various lengths and the three enzymes used in this study have different modular structures ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that preferential binding of cellulosomal enzymes to the cohesin modules did not result from slight differences in the binding affinity between the cohesin and dockerin modules, but rather, resulted from differences in the length of the intercohesin linker: a shorter intercohesin linker promoted preferential binding. Furthermore, computational simulations of the C. thermocellum cellulosome assembled with three cellulosomal enzymes (Cbh9A, Cel5B, and Cel48S) suggested that large multimodular enzymes (Cbh9A) may bind more frequently to CipA than smaller, single-modular enzymes (Cel5B or Cel48S) (37). Because CipA contains intercohesin linkers of various lengths and the three enzymes used in this study have different modular structures ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After initial attempts of many authors to disassociate and reconstitute the cellulosome had failed, there were many efforts to reconstitute a cellulolytic "minicellulosome" from recombinant components (4,10,24,26). All of them used scaffoldin proteins with a limited number of cohesin-binding sites or a limited number of enzyme components (6,7,11,25,34,37).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of whole cellulosomal subunit depends upon the affinity of interaction between dockerin domains having duplicated sequences and cohesin domains containing repeated sequences, as this interaction provides the most favorable arrangement for the enzymes to act efficiently on the substrate . The heterogenous nature of cellulosomes is due to the variability in the interaction of cohesin-dockerin moieties with difference in the amount of cohesin repeats, nature of enzymes bound to the scaffolding protein and species-specific variations (Bomble et al 2011;Koukiekolo et al 2005;Doi and Kosugi 2004;Fierobe et al 2005).…”
Section: Cohesin and Dockerinmentioning
confidence: 99%
“…The cellulosomal microorganisms can vary the composition of various catalytic subunits according to the substrate available to them (Cho et al 2010;Blouzard et al 2010;Tsai et al 2010). A variety of cellulosomes with variable composition can be assembled on a single species with various enzymes bound to the scaffolding protein (Bomble et al 2011). …”
Section: Cellulosomal Enzymesmentioning
confidence: 99%